PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, TAX PLANNING, DAN PROFITABILITY TERHADAP TAX AVOIDANCE: STUDI EMPIRIS PADA PERUSAHAAN SEKTOR ENERGI BERDASARKAN IDX-IC - Puspita Suci Prasetyana; Yuli Tri Cahyono (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine the effect of the implementation of good corporate governance, tax planning, and profitability on tax avoidance in energy sector companies based on the IDX-IC for the 2021-2023 period. The type of research is quantitative. The sampling technique used in this study is purposive sampling. A total of 85 companies have met the criteria as observation units. The analysis method used is multiple linear regression. The results of the study provide empirical evidence that tax planning has an effect, while audit quality, audit committee, and profitability have no effect on tax avoidance